Legal Protection for Bank Customers Who are Victims of Electronic Information Technology Crimes in the Banking Sector in Jayapura City - Pelupessy, Eddy; Kaplele, Farida (Journal of Law, Politic and Humanities, 2025)
Banking crimes are increasing, and perpetrators do it in various ways that can ultimately harm customers. The purpose of this study is to find out and analyze how related laws protect customers who are victims of ITE crimes in the banking sector and how banks are responsible for these customers. This study uses a normative legal method, which means research in the legal field that uses secondary data. This secondary data includes laws and regulations, court decisions, legal theories, and scholarly opinions. The results of this study indicate that adequate legal protection for victims of crime is a national and international problem. Therefore, the importance of protecting victims of violations is recognized. Legal protection for victims of crime is a protection of human rights or a person's legal interests that should receive special attention. This is important because crime and its victims are increasingly complex along with the progress of today's civilization. Therefore, banking institutions and consumer institutions can work together to create agreement clauses that meet the needs of the parties and do not violate the element of propriety. In addition, banks monitor employee behavior periodically to find indications of violations of the law.